2009
DOI: 10.1074/jbc.m109.001875
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Na+/H+ Antiporter NhaS3 from the Thylakoid Membrane of Synechocystis sp. PCC 6803

Abstract: Na؉ /H ؉ antiporters influence proton or sodium motive force across the membrane. Synechocystis sp. PCC 6803 has six genes encoding Na ؉ /H؉ antiporters, nhaS1-5 and sll0556. In this study, the function of NhaS3 was examined. NhaS3 was essential for growth of Synechocystis, and loss of nhaS3 was not complemented by expression of the Escherichia coli Na ؉ /H ؉ antiporter NhaA. Membrane fractionation followed by immunoblotting as well as immunogold labeling revealed that NhaS3 was localized in the thylakoid memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 50 publications
3
69
0
Order By: Relevance
“…We used E. coli as a heterologous expression system, as CHX23 failed to rescue growth of alkalinesensitive KTA40-2 yeast mutants. Interestingly, transporters associated with endomembranes in plant cells can be functionally expressed on the PM of E. coli (Uozumi, 2001;Tsunekawa et al, 2009;S. Chanroj and H. Sze, unpublished data).…”
Section: Cellular Role Of Chx23mentioning
confidence: 99%
“…We used E. coli as a heterologous expression system, as CHX23 failed to rescue growth of alkalinesensitive KTA40-2 yeast mutants. Interestingly, transporters associated with endomembranes in plant cells can be functionally expressed on the PM of E. coli (Uozumi, 2001;Tsunekawa et al, 2009;S. Chanroj and H. Sze, unpublished data).…”
Section: Cellular Role Of Chx23mentioning
confidence: 99%
“…1 and Table 1). Interestingly, the peak of the expression of aqpZ corresponded to early subjective night, which is similar to the circadian profile of the Na ϩ /H ϩ antiport system NhaS3 in Synechocystis, which is known to be involved in osmoregulation (48).…”
Section: Discussionmentioning
confidence: 61%
“…This difference may be the result of the Na ϩ adaptive system in Synechocystis. It has been reported that Synechocystis regulates Na ϩ influx and efflux across the plasma membrane and the thylakoid membrane via an Na ϩ transport system, e.g., an Na ϩ /H ϩ antiporter, in order to control ion homeostasis in the cytosol (11,21,33,48). In addition to the Na ϩ cycling system, NaCl also induces synthesis of the osmolyte glucosylglycerol in Synechocystis (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2G and Table 1). The full recovery of volume probably needs the synthesis and accumulation of the compatible solute glucosylglycerol in the second or later phase of osmoacclimation, which in- (57), nhaS3 (Na ϩ /H ϩ antiporter) (56), and mscL (mechanosensitive channel large conductance) (58) are also indicated (filled circles). duced more water influx and recovery of cell volume (4,5).…”
Section: Discussionmentioning
confidence: 99%